Tailoring CO2 detection capabilities using Co-ZnO/MoS2 nanocomposites through electrolyte concentration modulation - Swathi Yempally (17886686) (2024)
The current study explores a new approach to investigate the CO2 detection capabilities of cobalt-doped zinc oxide (Co-ZnO) combined with molybdenum sulfide (MoS2) hybrid nanomaterials Co-ZnO/MoS2 (CZM). The hydrothermally synthesized CZM composites provide unique structural and compositional properties, with 25 nm as their longest dimension (length), and specific lattice structure. CZM-based electrodes are developed by preparing the nanomaterial-dispersed ink, and potentiometric studies explore the optimal sensing performance. We found significant enhancements in sensitivity, reaction time, and reduction efficiency by systematically changing the electrolyte concentration in the electrode cell. Bode and Nyquist plots explain the influence of electrolyte concentration and the nanomaterial synergy in CO2 sensing and conversion with the 0.1 N electrolyte with the maximum efficiency. By offering important insights into how the electrolyte content affects the performance of Co-ZnO/MoS2 nanocomposite sensors, this study advances the field of CO2 sensing technology. Further, the nanomaterials extend their applicability in environmental monitoring, evaluating indoor air quality, and industrial processes. Other Information Published in: Journal of Materials Science License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10853-024-10331-1